2015
DOI: 10.2131/jts.40.701
|View full text |Cite
|
Sign up to set email alerts
|

Tris-(2,3-dibromopropyl) isocyanurate induces depression-like behaviors and neurotoxicity by oxidative damage and cell apoptosis <i>in vitro</i> and <i>in vivo </i>

Abstract: -Tris-(2,3-dibromopropyl) isocyanurate (TDBP-TAZTO), an emerging brominated flame retardant, possesses the characteristics of candidate persistent organic pollutants and has displayed toxicity to fish and rodents. TDBP-TAZTO can pass through the blood-brain barrier and accumulate in the brain. TDBP-TAZTO might also induce neuronal cell toxicity. However, the neurotoxicity and mechanisms of TDBP-TAZTO have not yet been studied. We hypothesize that TDBP-TAZTO could induce neurotoxicity in mouse hippocampal neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 22 publications
(29 reference statements)
4
25
0
Order By: Relevance
“…The reports show that the production of household materials such as electronics or plastic causes the release of many toxic substances, such as BFRs (Li et al 2015). BFRs are able to cross the blood-brain barrier and accumulate in animals' brains affecting their cells (Dong et al 2015). Therefore, due to the emerging problem of environmental pollution, in this study, we have determined the impact of TDBP-TAZTO on the neuron differentiation process in vitro and its engagement in the toxic mechanism in such cells.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The reports show that the production of household materials such as electronics or plastic causes the release of many toxic substances, such as BFRs (Li et al 2015). BFRs are able to cross the blood-brain barrier and accumulate in animals' brains affecting their cells (Dong et al 2015). Therefore, due to the emerging problem of environmental pollution, in this study, we have determined the impact of TDBP-TAZTO on the neuron differentiation process in vitro and its engagement in the toxic mechanism in such cells.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our results showed that TDBP-TAZTO at the concentrations of 1, 10, 50, and 100 µM decreased resazurin reduction in the undifferentiated cells and in cells differentiated for 7 and 14 days. There are only a few reports in the literature describing the in vivo and in vitro toxicity of TDBP-TAZTO (Ruan et al 2009;Li et al 2011;Dong et al 2015), but our study is the first to use the LDH release parameter to assess the toxicity of the compound. To date, an in vivo experiment has demonstrated that TDBP-TAZTO at a concentration of 1 µg/mL was toxic to developing zebrafish (Danio rerio) embryos after 72 h of exposure (Li et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations